2010
DOI: 10.3354/ame01398
|View full text |Cite
|
Sign up to set email alerts
|

High diversity of Rhodobacterales in the subarctic North Atlantic Ocean and gene transfer agent protein expression in isolated strains

Abstract: Genes encoding gene transfer agent (GTA) particles are well conserved in bacteria of the order Rhodobacterales. Members of this order are abundant in diverse marine environments, frequently accounting for as much as 25% of the total bacterial community. Conservation of the genes encoding GTAs allows their use as diagnostic markers of Rhodobacterales in biogeographical studies. The first survey of the diversity of Rhodobacterales based on the GTA major capsid gene was conducted in a warm temperate estuarine eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 42 publications
0
31
0
Order By: Relevance
“…The presence of GTA capsid proteins has been confirmed in multiple lineages within the order Rhodobacterales, from a range of geographically separated marine environments 46 . The possibility of widespread conservation of GTA production in this particular group of bacteria is especially interesting because roseobacters (within the order Rhodobacterales) appear to account for >25% of the total bacterial and archaeal community in some marine environments 47 .…”
Section: Cihr Author Manuscript Cihr Author Manuscriptmentioning
confidence: 96%
See 1 more Smart Citation
“…The presence of GTA capsid proteins has been confirmed in multiple lineages within the order Rhodobacterales, from a range of geographically separated marine environments 46 . The possibility of widespread conservation of GTA production in this particular group of bacteria is especially interesting because roseobacters (within the order Rhodobacterales) appear to account for >25% of the total bacterial and archaeal community in some marine environments 47 .…”
Section: Cihr Author Manuscript Cihr Author Manuscriptmentioning
confidence: 96%
“…As was the case in the work on R. pomeroyi GTAs 43 , no biochemical or genetic analysis was carried out for the R. nubinhibens GTA particles, nor was there a demonstration that GTA genes are required for the observed effects. Such experiments are needed to validate the proposed role of GTAs in the extraordinarily high frequencies of gene transfer reported.The presence of GTA capsid proteins has been confirmed in multiple lineages within the order Rhodobacterales, from a range of geographically separated marine environments 46 . The possibility of widespread conservation of GTA production in this particular group of bacteria is especially interesting because roseobacters (within the order Rhodobacterales) appear to account for >25% of the total bacterial and archaeal community in some marine environments 47 .…”
mentioning
confidence: 96%
“…GTAs are novel virus-like elements that function in the transfer of random fragments of genomic DNA (4.5 kb for the Rhodobacter capsulatus GTA) while conferring no documented negative effects associated with transfer (i.e., cell lysis) (10,38). While the g5 phylogeny has previously been found to be congruent with the 16S rRNA phylogeny (94), a more recent study of Rhodobacterales GTAs from the subarctic North Atlantic demonstrated that using a subset of the gene sequence information does not necessarily reflect the expected phylogenetic relationships (25). Analysis of the PRT1 g5 capsid protein with 156 available Rhodobacterales g5 capsid protein sequences (see Fig.…”
Section: Resultsmentioning
confidence: 93%
“…4). Two of them (phylogroups E and F) belonged to the Rhodobacterales that is one of the most common alphaproteobacterial order in polar and subpolar oceans (Fu et al, 2010;Ghiglione and Murray, 2012;Niederberger et al, 2010;Prabagaran et al, 2007;Salka et al, 2008;Selje et al, 2004). Loktanella-like puf M clones (phylotype F) dominated the libraries at both seasons, whereas proportions of Sulfitobacter-related sequences (phylogroup E) increased in winter.…”
Section: Diversity In the Arctic Oceanmentioning
confidence: 99%